(untitled) (Research, Society and Development, 2023)
Adenomyosis is a benign gynecological condition, characterized by the presence of stroma and endometrial glands in the myometrium, and can be characterized in subtypes, such as focal, diffuse, deep and superficial. The etiopathogenesis is still not fully elucidated, but the two most accepted theories involve invagination of the basal layer of the endometrium into the myometrium and de novo metaplasia of the Mullerian ducts. The diagnosis, which was formerly histopathological, after performing a hysterectomy, can now be made by imaging tests, with transvaginal ultrasound being the first-line test. The evolution of the diagnosis represented a watershed for the classification of this pathogenesis, due to the better characterization of the epidemiological data, the possibility of a better detailing of the clinical picture and the opportunity to more accurately identify these women in earlier stages of life, which meant that the treatment is now individualized, according to the wishes, especially in relation to fertility, of women. Thus, the objective of this study is to analyze what is most recent in the medical scenario about adenomyosis, aiming to provide better care for patients who have this disease.